Analisis Penerimaan Hadiah dan atau Janji Oleh Penjabat Negara Yang Terkategori Gratifikasi Dan Atau Suap Yang Terkagori Tindak Pidana - Kesuma, Derry Angling; Amin, Muhammad Nur; Afriani, Kinaria (Lex Librum : Jurnal Ilmu Hukum, 2025)
Gifts and/or promises to state officials that constitute criminal acts of corruption include: Giving gifts or parcels to officials during religious holidays by colleagues or subordinates; Gifts or donations during the wedding of an official's child by colleagues of the official; The provision of travel tickets to officials or their families for personal use free of charge; The provision of special discounts for officials for the purchase of goods from partners; The provision of fees or costs for the hajj pilgrimage from partners to officials; The provision of birthday gifts or gifts for other personal occasions from partners; The provision of gifts or souvenirs to officials during work visits; The giving of gifts or money as a token of gratitude for assistance. The legal basis for gratuities is regulated in Article 12 B of Law No. 20 of 2001 concerning amendments to Law No. 31 of 1999 concerning criminal acts of corruption. Article 12 B paragraph (1) of Law No. 31 of 1999 Jo. Law No. 20 of 2001. Reporting the receipt of gratuities to the Corruption Eradication Commission (KPK) for recipients of such gratuities is not punishable on the grounds that the unlawful nature of the act has disappeared. Acts of Reporting Gratuities That Can Make a Person Categorised as Not Committing a Criminal Act are when the recipient feels that the gift or gratuity is suspicious, they are obliged to report it to the Corruption Eradication Commission no later than 30 working days from the date the gratuity or gift was given.